2007
DOI: 10.1016/j.bbamem.2006.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Modular determinants of antimicrobial activity in platelet factor-4 family kinocidins

Abstract: Mammalian platelets contain an array of antimicrobial peptides, termed platelet microbicidal proteins (PMPs). Human and rabbit PMPs include known chemokines, such as platelet factor-4 (hPF-4); PMP-1 is the rabbit orthologue of hPF-4. Chemokines that also exert direct antimicrobial activity have been termed kinocidins. A consensus peptide domain library representing mammalian PF-4 family members was analyzed to define structural domains contributing to antimicrobial activity against a panel of human pathogens. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
80
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 75 publications
(81 citation statements)
references
References 61 publications
(151 reference statements)
1
80
0
Order By: Relevance
“…We previously discovered that human PMPs include the CXC chemokines platelet factor 4 and platelet basic peptide and derivatives, such as connective tissue-activating peptide 3 (CTAP-3) and interleukin-8, as well as the CC chemokine RANTES (released upon activation, normal T-cell expressed and secreted) (34,37,43). Microbicidal chemokines from platelets have been termed platelet kinocidins (PKs) (45), reflecting dual and complementary host defense roles likely bridging innate and adaptive immunity.…”
mentioning
confidence: 99%
“…We previously discovered that human PMPs include the CXC chemokines platelet factor 4 and platelet basic peptide and derivatives, such as connective tissue-activating peptide 3 (CTAP-3) and interleukin-8, as well as the CC chemokine RANTES (released upon activation, normal T-cell expressed and secreted) (34,37,43). Microbicidal chemokines from platelets have been termed platelet kinocidins (PKs) (45), reflecting dual and complementary host defense roles likely bridging innate and adaptive immunity.…”
mentioning
confidence: 99%
“…Human ␤-defensin 2 (h␤D-2; Peptides International) is a predominant host defense peptide (HDP) elaborated by epithelial tissues throughout the body. The mimetic peptide RP-1 is a synthetic 18-amino-acid congener engineered in part from the microbicidal ␣-helix domains of the platelet factor 4 family of kinocidins (8). RP-1 was synthesized, purified, and authenticated as previously detailed (9).…”
Section: Methodsmentioning
confidence: 99%
“…RP-1 was synthesized, purified, and authenticated as previously detailed (9). Each study peptide has demonstrated in vitro antimicrobial activity against S. aureus (3,7,8,10). sEL sensor domain.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations